2015
DOI: 10.1016/j.pcad.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Physical Activity and Health Care Expenditures in the United States

Abstract: This study estimates the percentage of health care expenditures in the non-institutionalized United States (U.S.) adult population associated with levels of physical activity inadequate to meet current guidelines. Leisure-time physical activity data from the National Health Interview Survey (2004–2010) were merged with health care expenditure data from the Medical Expenditure Panel Survey (2006–2011). Health care expenditures for inactive (i.e., no physical activity) and insufficiently active adults (i.e., som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
232
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(247 citation statements)
references
References 24 publications
10
232
1
4
Order By: Relevance
“…11,12 There is an acute awareness by governments, professional organizations and healthcare systems that being physically inactive, carrying excess body weight, and poor dietary choices are primary drivers for chronic disease…”
Section: Introductionmentioning
confidence: 99%
“…11,12 There is an acute awareness by governments, professional organizations and healthcare systems that being physically inactive, carrying excess body weight, and poor dietary choices are primary drivers for chronic disease…”
Section: Introductionmentioning
confidence: 99%
“…Clearly great efforts are needed to increase CR penetration in healthcare systems across the globe, given these are highly cost-effective strategies [100][101][102][103] . The next most commonly-offered component was patient education, which was delivered particularly often in North America, as well as the Middle East and North Africa.…”
mentioning
confidence: 99%
“…Parenthetically, research from a prominent tracking study, conducted over 21 years, that assessed physical activity from childhood through to adulthood found that high levels of continuous physical activity among youth predicted a high level of physical activity in adulthood [18]. As such, by establishing regular physical activity during the formative years of childhood appears to have downstream effects on physical activity later in life; with physical activity in adulthood not only related to improvements in psychological and physical health [19], but also reduced health care costs (recent estimates indicate that physical inactivity in adulthood accounts for 11.1 % ($117 billion) of aggregate health care expenditure per year in the USA) [20].…”
Section: Practice and Public Health Policiesmentioning
confidence: 99%